The last victim : a novel - Robards, Karen (Ballantine Books, 2012)
Investigating the brutal murders of two vacationing families in sunny Virginia Beach, FBI agents Ryan Sinclair and Buzz Crane suspect the work of a notorious serial killer and tap the skills of preeminent clinical expert Charlotte Stone, who is also the culprit's only known survivor.